2006
DOI: 10.1111/j.1399-3038.2006.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Ding Chuan Tang, a Chinese herb decoction, could improve airway hyper‐responsiveness in stabilized asthmatic children: a randomized, double‐blind clinical trial*

Abstract: Traditional Chinese medicine has a long history of application in the treatment of bronchial asthma. Solid scientific evidence, however, is not available despite its widespread use among patients worldwide and in Taiwan. To assess the effect of Ding Chuan Tang (DCT) in airway hyper-responsiveness (AHR) on asthmatic children via randomized, double blind, placebo-controlled clinical trial. This study enrolled children who were aged 8-15 and diagnosed as mild to moderate persistent asthma patients. They were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 28 publications
(36 reference statements)
2
84
1
4
Order By: Relevance
“…The oral administration of Japanese herbal complex Saiboku-to (TJ-96) significantly decrease asthma symptoms, blood eosinophils and serum eosinophilic cationic protein (Urata et al, 2002). In addition, herb decoction could improve airway hyper-responsiveness in stabilized asthmatic children (Chan et al, 2006). More interestingly, we highlighted that herbal leaves and root were more utilized for the healing of asthma.…”
Section: Discussionmentioning
confidence: 82%
“…The oral administration of Japanese herbal complex Saiboku-to (TJ-96) significantly decrease asthma symptoms, blood eosinophils and serum eosinophilic cationic protein (Urata et al, 2002). In addition, herb decoction could improve airway hyper-responsiveness in stabilized asthmatic children (Chan et al, 2006). More interestingly, we highlighted that herbal leaves and root were more utilized for the healing of asthma.…”
Section: Discussionmentioning
confidence: 82%
“…In 2006 Chan et al [19] reported that Ding Chuan Tang (DCT), a Chinese herbal decoction, could reduce AHR in stabilized asthmatic children in a randomized, double-blind clinical trial. DCT contains 9 herbs (Table I).…”
Section: Ding Chuan Tangmentioning
confidence: 99%
“…Chan et al (19) reported that in a randomized, double-blind clinical trial, Ding Chuan Tang (DCT), a nine herb formula, reduced airway hyper-reactivity (AHR) in stabilized asthmatic children. (Table I).…”
Section: Ding Chuan Tang (Dct)mentioning
confidence: 99%